2019
DOI: 10.3390/languages4030068
|View full text |Cite
|
Sign up to set email alerts
|

Language and Math: What If We Have Two Separate Naming Systems?

Abstract: The role of language in numerical processing has traditionally been restricted to counting and exact arithmetic. Nevertheless, the impact that each of a bilinguals' languages may have in core numerical representations has not been questioned until recently. What if the language in which math has been first acquired (LL math ) had a bigger impact in our math processing? Based on previous studies on language switching we hypothesize that balanced bilinguals would behave like unbalanced bilinguals when switching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 126 publications
(192 reference statements)
0
3
0
Order By: Relevance
“…Language differences only arose when subjects were required to work in both languages a single session (i.e., language switching). An asymmetric switching effect has also been observed for number word reading in bilingual adults [34].…”
Section: Language Of Learning Effectsmentioning
confidence: 66%
See 1 more Smart Citation
“…Language differences only arose when subjects were required to work in both languages a single session (i.e., language switching). An asymmetric switching effect has also been observed for number word reading in bilingual adults [34].…”
Section: Language Of Learning Effectsmentioning
confidence: 66%
“…In fact, one study investigating language preference in simple arithmetic showed that a preference for the LA+ only occurred when the trials switched between languages, but not when the trials were blocked by language [33]. An asymmetric switching effect has also been observed for number word reading in bilingual adults [34].…”
Section: Introductionmentioning
confidence: 99%
“…That is why it was easier and faster for his brain to switch to English, to perform the familiar counting operation in this language. This fact is supported by the bilingual research on Math cognition, which has demonstrated that bilinguals feel more comfortable and perform better in the language in which they have learnt arithmetic in school (Marsh & Maki, 1976;Martinez, 2019). The same explanation can be used for code-switching of the word "fraction" into English, line 36.…”
Section: Dialogue 2 "My Next Semester"mentioning
confidence: 84%